Math toppers answer the questions........
correct answer will be marked as brainlist
Attachments:
![](https://hi-static.z-dn.net/files/d28/288233051ed87889f5d48f24a2cbef9d.jpg)
Answers
Answered by
1
1) cos θ/(1 - tan θ) + sin θ/(1 - cot θ) = sin θ + cos θ
Solution:
L.H.S = cos θ/(1 - tan θ) + sin θ/(1 - cot θ)
= cos θ/{1 - (sin θ/cos θ)} + sin θ/{1 - (cos θ/sin θ)}
= cos θ/{(cos θ - sin θ)/cos θ} + sin θ/{(sin θ - cos θ/sin θ)}
= cos2 θ/(cos θ - sin θ) + sin2 θ/(cos θ - sin θ)
= (cos2 θ - sin2 θ)/(cos θ - sin θ)
= [(cos θ + sin θ)(cos θ - sin θ)]/(cos θ - sin θ)
= (cos θ + sin θ) = R.H.S. Proved.
Similar questions